Characteristic of surface pressure around an aerofoil in plunging motion [electronic resource] - Abd. Latip Md. Ali, 1987- (2010)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal - Aeronautik)) - Universiti Teknologi Malaysia, 2010